The influence of feed rate and shear forces on the devulcanization process of ground tire rubber (GTR) conducted in a co-rotating twin screw extruder - Formela, K.; Cysewska, M; Haponiuk, J.; Stasiek, A. (Polimery, 2013)
The search for new ways to recycling of rubber waste has been the aim of many studies conducted by research centers and companies worldwide. The results of our investigations on the process of continuous thermomechanical devulcanization of ground tire rubber using a twin screw extruder are presented. We used a co-rotating twin screw extruder with a special configuration of plasticizing unit, enabling generation of considerable shear forces. Various properties were characterized, such as the influence of the ground tire rubber feed rate and screw speed (shear forces) on the screw torque, acetone extract, sol fraction, and the degree of devulcanization in the resulting products. The effect of a secondary vulcanization on the vulcametric curves was determined, and the mechanical properties (tensile strength, elongation at break, hardness, resilience and abrasion resistance) of the revulcanized material were studied. It has been determined that the devulcanization process depends on the values of shear force and residence time acting on ground tire rubber. The devulcanization degree increases with increasing screw speed and feed rate. The results of repeatability of continuous devulcanization process of ground tire rubber were also determined. Obtained products possess the quality comparable to that of reclaim rubber available on the market.